2019
DOI: 10.3390/nu11010085
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutrients in Reducing the Risk for Noncommunicable Diseases during Aging

Abstract: An increasing aging population worldwide accounts for a growing share of noncommunicable diseases (NCDs) of the overall social and economic burden. Dietary and nutritional approaches are of paramount importance in the management of NCDs. As a result, nutrition programs are increasingly integrated into public health policies. At present, programs aimed at reducing the burden of NCDs have focused mostly on the excess of unhealthy nutrient intakes whereas the importance of optimizing adequate essential and semi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 130 publications
0
110
0
6
Order By: Relevance
“…Lifestyle, including dietary habits, is a determining factor of the high incidence and prevalence of chronic non-communicable diseases (NCDs), such as cardiovascular disease (CVD), diabetes and dementia [1]. Several studies have shown that non-smokers, the practice of physical activity, having an adequate body mass index (BMI) and a healthy diet pattern (rich in vegetables, fruits, legumes and fish, and limited in red meat), with moderate alcohol consumption, are factors associated with a lower risk of mortality by all causes and CVD (≥65%) compared to subjects who have an unhealthy lifestyle [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle, including dietary habits, is a determining factor of the high incidence and prevalence of chronic non-communicable diseases (NCDs), such as cardiovascular disease (CVD), diabetes and dementia [1]. Several studies have shown that non-smokers, the practice of physical activity, having an adequate body mass index (BMI) and a healthy diet pattern (rich in vegetables, fruits, legumes and fish, and limited in red meat), with moderate alcohol consumption, are factors associated with a lower risk of mortality by all causes and CVD (≥65%) compared to subjects who have an unhealthy lifestyle [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Among older adults, micronutrient inadequacy and deficiency elicit a variety of consequences, including a reduced ability to resist infection, impaired cognitive function, and increased risk for chronic disease, thereby reducing the health span (Bruins et al 2019). For example, nutrient deficiency in patients with heart failure is a significant determinant of heart failure outcomes (Lennie et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…19 In order to reduce risks associated with chronic diseases, changes in diet, such as reducing fat and simple carbohydrates, are encouraged and can result in weight loss. 20,21 In the case of arthropathies, for instance, intentional weight loss of >10% provides important clinical benefits. 21 On the other hand, physiological changes that promote catabolic and inflammatory stress and greater energy expenditure, 22 as in the case of pulmonary diseases, can result in unintentional weight loss and cause the health condition of the more elderly to worsen.…”
Section: Supplement 1 -Flowchart Of Total Population and Losses Durinmentioning
confidence: 99%